Empiric piperacillin-tazobactam versus carbapenems in the treatment of bacteraemia due to extended-spectrum beta-lactamase-producing enterobacteriaceae - Ng T.M. (Public Library of Science (PLoS), 2018)
10.1371/journal.pone.0153696